Biofilm Formation and Aspartyl Proteinase Activity and Their Association with Azole Resistance Among Candida albicans Causing Vulvovaginal Candidiasis, Egypt - Gerges MA; Fahmy YA; Hosny T; Gandor NH; Mohammed SY; Mohamed TMA; Abdelmoteleb NEM; Esmaeel NE (Infection and Drug Resistance, 2023)
Marian A Gerges,1 Yasmin Ahmed Fahmy,1 Thoraya Hosny,2 Nessma H Gandor,2 Sherif Y Mohammed,2 Tahia Mohamed Ahmed Mohamed,2 Nabila Elsayed Mousa Abdelmoteleb,3 Noura E Esmaeel1 1Medical Microbiology and Immunology Department, Faculty of Medicine, Zagazig University, Zagazig, Egypt; 2Clinical Pathology Department, Faculty of Medicine, Zagazig University, Zagazig, Egypt; 3Gynecology and Obstetrics Department, Faculty of Medicine, Zagazig University, Zagazig, EgyptCorrespondence: Marian A Gerges, Medical Microbiology and Immunology Department, Faculty of Medicine, Zagazig University, Zagazig, 44519, Egypt, Tel +2 01003819530, Email MAGerges@zu.edu.egBackground: Candida albicans (C. albicans) is a major cause of vulvovaginal candidiasis (VVC), a condition that is commonly treated with azole agents. Biofilm formation and aspartyl proteinase production are important virulence factors that could be linked to azole resistance in C. albicans impeding therapy.Aim: To find out the association of both factors with azole resistance among C. albicans isolated from VVC cases in Egyptian nonpregnant women of childbearing age.Patients and Methods: In a cross-sectional study, C. albicans was isolated from nonpregnant females diagnosed clinically as having VVC during a 1-year study period. Susceptibility to azole agents was tested using the disc diffusion method. Biofilm formation and aspartyl proteinase production were assessed phenotypically. Additionally, two biofilm-related genes (ALS1 and HWP1) and three proteinase genes (SAP2, SAP4, and SAP6) were screened for using polymerase chain reaction (PCR).Results: Among 204 C. albicans isolates, azole resistance ratios were as follows: voriconazole (30.4%), itraconazole (17.6%), fluconazole (11.3%) and econazole (6.4%). Biofilm-producing capacity was detected in 63.2% of isolates, and 63.2% were proteinase producers. The frequencies of ALS1 and HWP1 were 69.6% and 74.5%, respectively, while SAP2, SAP4, and SAP6 were 69.2%, 88.7%, and 64.7%, respectively. Biofilm formation was significantly associated with azole resistance (P < 0.001 for each tested azole agent) as was proteinase production (P < 0.001 for fluconazole, voriconazole, and econazole resistance and P = 0.047 for itraconazole).Conclusion: Among nonpregnant Egyptian women of childbearing age, azole resistance in C. albicans causing VVC is significantly associated with biofilm formation and proteinase production. The development of new therapeutic agents that can target these factors is warranted.Keywords: Candida albicans, vulvovaginal candidiasis, biofilm formation, aspartyl proteinase, azole resistance